Regulating Cofactor Balance In Vivo with a Synthetic Flavin Analogue. Issue 50 (14th November 2018) - Tan, Zhuotao; Zhu, Chenjie; Fu, Jingwen; Zhang, Xiaowang; Li, Ming; Zhuang, Wei; Ying, Hanjie
Abstract: A novel strategy to regulate cofactor balance in vivo for whole‐cell biotransformation using a synthetic flavin analogue is reported. High efficiency, easy operation, and good applicability were observed for this system. Confocal laser scanning microscopy was employed to verify that the synthetic flavin analogue can directly permeate into Escherichia coli cells without modifying the cell membrane. This work provides a promising intracellular redox regulatory approach to construct more efficient cell factories. Abstract : Balancing act : A novel strategy to manipulate the intracellular cofactor balance for whole‐cell biotransformations based on a synthetic flavin analogue is reported. The synthetic flavin analogue can directly permeate into E. coli cells and accelerate cellular NAD + regeneration without requiring cell‐membrane modification.